2022
DOI: 10.1140/epjs/s11734-022-00727-y
|View full text |Cite
|
Sign up to set email alerts
|

Paper based microfluidic devices: a review of fabrication techniques and applications

Abstract: A wide range of applications are possible with paper-based analytical devices, which are low priced, easy to fabricate and operate, and require no specialized equipment. Paper-based microfluidics offers the design of miniaturized POC devices to be applied in the health, environment, food, and energy sector employing the ASSURED (Affordable, Sensitive, Specific, User-friendly, Rapid and Robust, Equipment free and Deliverable to end users) principle of WHO. Therefore, this field is growing very rapidly and ample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 223 publications
0
22
0
Order By: Relevance
“…Most of the PμFCs fed by biomass-derived alcohols reported here are also higher than those reported in the literature, even considering other fuels and oxidants . Under our knowledge, the systems that deliver higher power density than reported here are fed by other liquids, such as formic acid, potassium formate in stacks, zinc and vanadium, and others detailed by Tanveer et al Moreover, the PμFC reported here may benefit further from an improved design, such as folding, adding patterns to change the flow mechanism, changing the size of electrodes, and flow configuration …”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Most of the PμFCs fed by biomass-derived alcohols reported here are also higher than those reported in the literature, even considering other fuels and oxidants . Under our knowledge, the systems that deliver higher power density than reported here are fed by other liquids, such as formic acid, potassium formate in stacks, zinc and vanadium, and others detailed by Tanveer et al Moreover, the PμFC reported here may benefit further from an improved design, such as folding, adding patterns to change the flow mechanism, changing the size of electrodes, and flow configuration …”
Section: Resultsmentioning
confidence: 46%
“…The PμFC was designed in a simple and well-known architecture, aiming to investigate the use of biomass-derived fuels as the sole variable. A similar design can be found elsewhere, and the mechanism of fluid transport throughout the paper is based on the capillarity of the cellulose paper, without intricate sets of hydrophilic/hydrophobic patterns …”
Section: Methodsmentioning
confidence: 99%
“…Many research organizations collaborate with industrial partners, but actual commercialization is still lacking (Trinh et al, 2022). Large‐scale printing methods should be investigated to fabricate µPADs that are low in cost, high in resolution, and have simple process steps (Anushka et al, 2022).…”
Section: Market Demand and Future Prospectsmentioning
confidence: 99%
“…The use of μPADs has several advantages over traditional diagnostic techniques, such as being low cost, ease of use, and portable. [18][19][20][21][22] The wicking of the liquid through the porous matrix in μPADs promotes the transport of the sample and facilitates the mixing of the sample with reagents, enabling the detection of target analytes. μPADs have been utilized for a wide range of applications, including detection of infectious diseases, environmental monitoring, and food safety testing.…”
Section: Introductionmentioning
confidence: 99%
“…μPADs have been utilized for a wide range of applications, including detection of infectious diseases, environmental monitoring, and food safety testing. 22 Understanding liquid wicking in porous media is crucial in the development of new and efficient μPADs. By optimizing the properties of the porous material, such as pore size and shape, and the composition of the reagents, the performance of the device can be enhanced, leading to more sensitive and accurate detection of target analytes.…”
Section: Introductionmentioning
confidence: 99%